2022
DOI: 10.3390/brainsci12070951
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus with Tight Glucose Control and Poor Pre-Injury Stair Climbing Capacity May Predict Postoperative Delirium: A Secondary Analysis

Abstract: (1) Background: Previous evidence demonstrates that tight glycemic control and good physical function could reduce the risk of delirium. This study aimed to investigate whether the occurrence of postoperative delirium (POD) in older hip fracture surgery patients is associated with preoperative glycemic control factors or pre-injury physical performance. (2) Methods: Three-hundred and nine individuals aged over 65 years and scheduled for hip fracture surgery were included at a single center. Glycemic control fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In line with previous studies, 11,12 our findings support the notion that preoperative diabetes is a significant predictor of POD in elderly patients undergoing major orthopedic surgery. In contrast to recently published work which were retrospective studies without match, 29,30 the strength of the current study is its prospective matched cohort design with preoperative diabetes as the primary exposure, which minimizes confounding from age, sex, and surgery type. Another strength is the well identification of diabetes, with all diabetics confirmed with a known history or a new preoperative diagnosis, which decreased the likelihood of missed diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies, 11,12 our findings support the notion that preoperative diabetes is a significant predictor of POD in elderly patients undergoing major orthopedic surgery. In contrast to recently published work which were retrospective studies without match, 29,30 the strength of the current study is its prospective matched cohort design with preoperative diabetes as the primary exposure, which minimizes confounding from age, sex, and surgery type. Another strength is the well identification of diabetes, with all diabetics confirmed with a known history or a new preoperative diagnosis, which decreased the likelihood of missed diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed a close association between diabetes and cognitive dysfunction, including dementia and Alzheimer’s disease. This association may be driven by factors such as insulin resistance, altered glucose metabolism, vascular changes, and the metabolism of β-amyloid and tau [ 32 34 ].In our study, the relevant p value ( P = 0.047 ) was unfortunately close to 0.05, which may be attributed to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Long-term excessive drinking or alcoholism will lead to alcohol dependence, acute and chronic alcoholism, and extensive and severe damage to the central nervous system, including brain atrophy, toxic myopathy, multiple mental derangement, central nervous system degeneration, metabolic disease, and mental disorders. 15 , 16 The neuropsychological cognitive impairment caused by alcoholism, called alcohol-induced cognitive impairment, occurs in as many as 50%-80% of patients with alcohol dependence. 17 It is well known that cognitive function is a unique higher neural function of human beings, which involves multiple dimensions, including memory, understanding, attention, language, and executive function.…”
Section: Discussionmentioning
confidence: 99%